2019
DOI: 10.1016/j.ajoc.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Occipital tip injury with homonymous central scotoma: OCT-NFL and RGC correlation

Abstract: PurposeTo report one case of homonymous paracentral scotoma with corresponding optical coherence tomography (OCT) findings in a young woman after injury to the left occipital lobe tip.ObservationsA young woman with past medical history of Hodgkin's lymphoma and large B-cell lymphoma metastatic to the left occipital lobe status post resection presented to the eye clinic with a chief complaint of a “blind spot” in the right eye since her surgery. Humphrey visual field (HVF) showed a right homonymous paracentral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The diagnostic criteria of retrograde degeneration are not yet established. The pattern and form of retrograde degeneration in the retina as measured with OCT has been mainly based on case reports (Foster et al., 2019 ; Hokazono et al., 2019 ; Newman‐Wasser et al., 2019 ; Tatsumi et al., 2005 ). A few studies have shown that the retinal ganglion cell and inner plexiform layer (GCIPL) in the macula and their axons of retinal nerve fiber layer (RNFL) in the optic disc are reduced after retrochiasmal lesions (Jindahra et al., 2012 ; Keller et al., 2014 ; Park et al., 2013 ; Yamashita et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic criteria of retrograde degeneration are not yet established. The pattern and form of retrograde degeneration in the retina as measured with OCT has been mainly based on case reports (Foster et al., 2019 ; Hokazono et al., 2019 ; Newman‐Wasser et al., 2019 ; Tatsumi et al., 2005 ). A few studies have shown that the retinal ganglion cell and inner plexiform layer (GCIPL) in the macula and their axons of retinal nerve fiber layer (RNFL) in the optic disc are reduced after retrochiasmal lesions (Jindahra et al., 2012 ; Keller et al., 2014 ; Park et al., 2013 ; Yamashita et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%